The role of epigynal setae in mate choice in the orb-weaver Leucauge argyra. Issue 3 (4th May 2023) - Hernandez Duran, Linda; Barrantes, Gilbert
Abstract : Male and female genital morphology may have strong effects on fitness in spiders. Females of some species of Leucauge produce mating plugs that partially or totally block the entrances to their insemination ducts on the epigynum, forming barriers that reduce the probabilities of future inseminations. While in some species both females and males participate in plug formation, the mating plugs in L. argyra are produced exclusively by females. The epigynum of L. argyra (Walckenaer 1841) is unusual in having a prominent ventral process covered on its anterior side and around its base with long, thick setae. We tested whether male stimulation of these epigynal setae affected female plug formation by removing them from some females but not others. Females lacking setae produced mating plugs immediately after copulation less often than unmanipulated females. However, 24 hr later the mating plugs had disappeared in many females of the treatment group. Setae removal did not affect the amount of sperm stored in the female spermatheca, or the frequency of female attacks. The rate of male genital inflations correlated positively, but mating duration was negatively correlated with sperm stored in female's spermathecae. Females attempted to attack small males more often than large males. These findings contribute to our understanding of the function of the setae associated with the female genitalia, and the effect of their tactile stimulation on plug formation, and transference of spermatozoids. HIGHLIGHTS: Removal of female epigynal setae affects the frequency of female plug formation Male size influences female attack decisions during mating